Correlation Between Wood Dust Levels with Interleukin-8 in Blood Serum Wood Processing Workers at X Company, Tanjung Morawa - Jubilette Windy Hutabarat; Nuryunita Nainggolan; Amira Permatasari Tarigan; Putri Eyanoer (Jurnal Respirologi Indonesia, 2020)
Backgrounds: Wood dust exposure can stimulate proinflammatory cytokines and increase IL-8 levels, which is a foreign body in the body will be phagocytosis by macrophages and excrete mediators such as chemokines, cytokines, and chemoattractants which can cause inflammation. Duration of exposure, number and size of wood dust in the respiratory tract of wood industry workers are associated with various pulmonary disorders such as, COPD, occupational asthma, allergic rhinitis, decreased pulmonary function and pulmonary fibrosis. The aim this study is determine correlation between wood dust levels with interleukin-8 in blood serum among wood processing workers at x company, Tanjung Morawa-North Sumatera. Methods: A cross-sectional study which involved 40 workers from 3 different locations namely cutting, sanding and drafting. Cumulative wood dust exposure was calculated by measuring the dust content at the work site using Dusttrak TSI. IL-8 serum levels were measured using the ELISA technique. The Spearman correlation test was used. Results: Out of 40 workers those who worked in the cutting section were 15 people (37,5%), sanding section were 15 people (37,5%) and drafting section were 10 people (25%). The average level of wood dust PM 2,5 was 5,23 mg/m3while PM10 was 8,24 mg/m3 and the mean level of IL-8 in serum was 163,3 ng/L. This study find that there is a strong correlation between wood dust and IL-8 serum (r = 0,683; p